Numerical analysis of the optimum membrane/ionomer water content of PEMFCs: The interaction of Nafion® ionomer content and cathode relative humidity. (15th January 2015) - Xing, Lei; Das, Prodip K.; Song, Xueguan; Mamlouk, Mohamed; Scott, Keith
Highlights: Both membrane and ionomer swelling are considered into the two-phase flow agglomerate model. The interaction of dry ionomer content ( L M dry ) and cathode relative humidity ( RH c ) is investigated. The optimum RH c initially decreases then increases as L M dry increases at higher current densities. An 10% ionomer volume fraction and 75% cathode relative humidity yield the best cell performance. The optimum ionomer content and relative humidity improves the cell power density by 14.5%. Abstract: A two dimensional, across the channel, isothermal, two-phase flow model for proton exchange membrane fuel cells (PEMFCs) is developed to investigate the interaction of dry Nafion® ionomer volume fraction ( L M dry ) and cathode relative humidity ( RH c ) in PEMFCs. The agglomerate model is used to describe the catalyst layers properties, in which the agglomerate is covered by ionomer and liquid water films. The optimum ionomer water content is suggested by maximising the oxygen diffusion rate through the ionomer film. The effects of L M dry and RH c on membrane and ionomer swelling and the cell performance are studied. The predicted current densities at fixed cell voltages are analysed by the Kriging surrogate model and used to optimise the L M dry and RH c based on analysing their interaction. The simulation results show that the optimum ionomer water content increases as the ionomer content increases. At higher current densities, e.g. 1.0 A cm −2, the best cell performance is achieved with L M dry of 10%, corresponding to 0.3 mg cm −2, with fully humidified inlet gases. The optimum RH c is between 60% and 80% for L M dry of 40%. The modelling results also show that at higher current densities, the optimum RH c initially decreases then increases as L M dry increases. The optimum RH c decreases from 76% to 73% as L M dry increases from 10% to 30% then it increases up to 85% as L M dry increases to 50%.